2021
DOI: 10.1007/s00300-021-02911-7
|View full text |Cite
|
Sign up to set email alerts
|

Distinct genetic clustering in the weakly differentiated polar cod, Boreogadus saida Lepechin, 1774 from East Siberian Sea to Svalbard

Abstract: The cold-adapted polar cod Boreogadus saida, a key species in Arctic ecosystems, is vulnerable to global warming and ice retreat. In this study, 1257 individuals sampled in 17 locations within the latitudinal range of 75–81°N from Svalbard to East Siberian Sea were genotyped with a dedicated suite of 116 single-nucleotide polymorphic loci (SNP). The overall pattern of isolation by distance (IBD) found was driven by the two easternmost samples (East Siberian Sea and Laptev Sea), whereas no differentiation was r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 104 publications
3
8
0
Order By: Relevance
“…Alternatively, genetic division could have arisen from different breeding times or due to assortative mating (Potkamp and Fransen, 2019). Similar cryptic genetic subdivisions have recently been described for northern shrimp ( Pandalus borealis (Hansen et al, 2021)) and polar cod ( Boreogadus saida (Quintela et al, 2021). We ruled out the inherent weakness of clustering analyses favoring solution K =2 (Quintela et al, 2014; Janes et al, 2017) as a plausible explanation for the observed two-cluster model in the Arctic, as well as for mainland Norway (see below) for several reasons: First, groupings were far from equal in size nor were they randomly distributed but constantly found within certain samples.…”
Section: Discussionsupporting
confidence: 77%
“…Alternatively, genetic division could have arisen from different breeding times or due to assortative mating (Potkamp and Fransen, 2019). Similar cryptic genetic subdivisions have recently been described for northern shrimp ( Pandalus borealis (Hansen et al, 2021)) and polar cod ( Boreogadus saida (Quintela et al, 2021). We ruled out the inherent weakness of clustering analyses favoring solution K =2 (Quintela et al, 2014; Janes et al, 2017) as a plausible explanation for the observed two-cluster model in the Arctic, as well as for mainland Norway (see below) for several reasons: First, groupings were far from equal in size nor were they randomly distributed but constantly found within certain samples.…”
Section: Discussionsupporting
confidence: 77%
“…Alternatively, the genetic division could have arisen from different breeding times or from assortative mating [ 99 ]. Similar cryptic genetic subdivisions have recently been described for northern shrimp ( Pandalus borealis [ 100 ]) and polar cod ( Boreogadus saida [ 101 ]. We ruled out the inherent weakness of clustering analyses favoring solution K = 2 [ 102 , 103 ] as a plausible explanation for the observed two-cluster model in the Arctic, as well as for mainland Norway (see below) for several reasons: First, groupings were far from equal in size nor were they randomly distributed but constantly found within certain samples.…”
Section: Discussionsupporting
confidence: 71%
“…We identified four studies that met our criteria for inclusion, all of which were published within the last three years (Table 1). These studies targeted Pacific herring Clupea pallasii (Orlova et al, 2021;Petrou et al, 2021), polar/Arctic cod Boreogadus saida (Quintela et al, 2021), and Japanese anchovy Engraulis japonicus (Zhang et al, 2020), representing a fraction of the taxonomic diversity of forage fishes in the North Pacific as defined by AFSC (>50 species; 50 CFR Part 679). Of the four studies we reviewed, one lacked sufficient collection date information, providing only the year of sample collection, and sample collection depth was absent from all four studies.…”
Section: A Paucity Of Genomic Datamentioning
confidence: 99%
“…The investment that has gone into generating genomic data (Zhang et al, 2020;Orlova et al, 2021;Petrou et al, 2021;Quintela et al, 2021) and recording environmental observations in the North Pacific (AOOS, WOD, WorldClim) offers a novel opportunity to investigate GEAs post hoc. When investigating GEAs is not the explicit objective of a population genomics study, the collection of real-time environmental measures is frequently infeasible.…”
Section: Opportunities For Post Hoc Extensionmentioning
confidence: 99%